EL-YEZÎDIYYE VE AKÂIDUHÂ - MOHAMMED, YASEEN (Fırat Üniveristesi, 2018)
Yezidiler dünyanın en garip gruplarındandır. Her kim onların hakkında birşeyler öğrenmeye çalışırsa, paradokslarla yüzleşiyor. Bunların da bir kaç sebebi var. Onlardan biri cehalettir. Yezidiler toplumdan uzak kapalı bir şekilde yaşıyorlar. İbadetlerini insanların gözlerinden uzak bir şekilde yapıyorlar. Yezidiler Allaha, meleklere, kitaplara, peygamberlere, ahiret gününe ve kadere müslümanlarınkinden farklı bir şekilde inanmaktadırlar. Yezidiler kendilerine has bir şekilde namaz kılıyor, oruç tutuyor, hacca gidiyor ve zekat (sadaka) veriyor.

Yezidis are one of the most strange ethnic groups in the world. Anyone aims to know something about them, will find paradox notions. The reasons are being uneducational, things have been said about them are from others than themselves. They are a closed group. They perform their rituals and worships in secret. Yezidis have their own definitions for Faith, God, Angels, Holy Books, Prophets, The Day of Judgment. In some cases, they agree with the Muslims and in some cases they do not. Yezidis are serious about their own rituals, such as praying, fasting, pilgrimage and charity.
Yezidilik ve inançları
Keywords: Din